1995
DOI: 10.1029/94gb03103
|View full text |Cite
|
Sign up to set email alerts
|

Tropospheric budget of reactive chlorine

Abstract: Reactive chlorine in the lower atmosphere (as distinguished from chlorofluorocarbon‐derived chlorine in the stratosphere) is important to considerations of precipitation acidity, corrosion, foliar damage, and chemistry of the marine boundary layer. Many of the chlorine‐containing gases are difficult to measure, and natural sources appear to dominate anthropogenic sources for some chemical species. As a consequence, no satisfactory budget for reactive chlorine in the lower atmosphere is available. We have revie… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

15
300
2
4

Year Published

1999
1999
2015
2015

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 304 publications
(321 citation statements)
references
References 188 publications
15
300
2
4
Order By: Relevance
“…This is within the broad range of literature values derived from indirect measurements by e.g. relative rates of degradation of different hydrocarbons (also known as "hydrocarbon clock" observations), which give widely varying results ranging from 10 4 to 10 6 cm −3 in the MBL (Graedel and Keene, 1995), around or below 10 4 cm −3 in the global atmosphere (Singh et al, 1996), or 1.6·10 4 cm −3 (taking 1 / 4 of the noontime Cl concentration of 6.4·10 4 cm −3 derived from Lagrangian experiments in the North Atlantic conducted by Wingenter et al, 1996). Within the MBL, these concentrations would result in an effective KIE of −33 to −41‰.…”
Section: Discussionmentioning
confidence: 54%
“…This is within the broad range of literature values derived from indirect measurements by e.g. relative rates of degradation of different hydrocarbons (also known as "hydrocarbon clock" observations), which give widely varying results ranging from 10 4 to 10 6 cm −3 in the MBL (Graedel and Keene, 1995), around or below 10 4 cm −3 in the global atmosphere (Singh et al, 1996), or 1.6·10 4 cm −3 (taking 1 / 4 of the noontime Cl concentration of 6.4·10 4 cm −3 derived from Lagrangian experiments in the North Atlantic conducted by Wingenter et al, 1996). Within the MBL, these concentrations would result in an effective KIE of −33 to −41‰.…”
Section: Discussionmentioning
confidence: 54%
“…Emission fluxes of 50 Tg Cl yr −1 , 6 Tg Cl yr −1 , 4.6 Tg Cl yr −1 , and 2 Tg Cl yr −1 for HCl are emitted globally to the atmosphere from dechlorination of sea salt aerosols (Graedel and Keene, 1995;Keene et al, 1999), biomass burning , coal combustion and waste burning , respectively. As Beijing is ∼150 km from the sea, it has been demonstrated that the contribution to the aerosols from the sea could be ignored here (Yuan et al, 2004).…”
Section: Introductionmentioning
confidence: 99%
“…Research over the past several decades has shown that the presence of reactive gas phase chlorine species, particularly chlorine radicals (Cl • ), can contribute significantly to atmospheric reactivity [1][2][3][4][5][6][7]. High concentrations of Cl • can lead to increased rates of Volatile Organic Compound (VOC) oxidation [8][9][10][11][12][13] and enhanced rates of O3 production in the troposphere [1,3,7,[14][15][16].…”
Section: Introductionmentioning
confidence: 99%